Job Satisfactions of Quantity Surveyors in Building Construction Firms in Dar-Es-Salaam, Tanzania - Jaffari S. Jongo; Dennis N.G.A.K. Tesha; Raymond Kasonga; Valentine G.M., Luvara; Rebecca J. Mwanganda (International Journal of Engineering and Management Research, 2019)
Human resource is the key component for any organization’s success. It is crucial for organization to manage their human resources effectively and to their satisfaction, so that they stay longer without leaving the organization. Job satisfaction is identified as one of the factor that causes turnover intention of human resources in any organization. The study evaluates the job satisfaction of quantity surveyors in building construction firms of Dar-Es-salaam, Tanzania; with objectives being; to identify factors influencing job satisfaction; to determine level of job satisfaction; and to recommend interventions that can be applied to improve job satisfaction of quantity surveyors in building construction firms. The study considered a descriptive design where quantity surveyors employed by Class I to IV building construction firms were used, as a unit of analysis. In collecting data, a total of 55 questionnaires were distributed, whereby 42 were returned. Quantitative data were analyzed using Statistical Package for Social Sciences (SPSS), while qualitative data were analyzed thematically. The study revealed the major factors influencing job satisfaction of quantity surveyors, in order of importance, which includes; the working condition; organization commitment; pay; self-satisfaction of work done; job recognition; appreciation; relationship with co-workers; training and development opportunities; job security; job feedback; and job involvement in decision making and responsibilities. Furthermore, findings indicated that; the overall level of job satisfaction of quantity surveyors in building construction firms, is an average level of satisfaction with the mean score value of 3.02 and mode of 4.00. Moreover, it revealed that; quantity surveyors in building construction firm, have low level satisfaction in terms of job involvement in decision making and responsibilities; feedback and communication; job security; level of supervision; training and development opportunities; and the company’s promotion policies. Various interventions recommended to improve job satisfaction of quantity surveyors in building construction firms includes; adequate recognition of the work by the quantity surveyors in the construction firms should be fully appreciated, and encroachment by other professionals should be highly discouraged. Advancement opportunity in career progression and professional development should be encouraged to improve quality service delivery. The work to be done by quantity surveyors should have clear goals, while objectives and interference by other professionals should be checked.